Event management : theory and practice - Wrathall, Jeff; Gee, Abby (McGraw-Hill, 2011)
Provides coverage of the most important competency units of Certificate III and Diploma of Events in the SIT07 Tourism, Hospitality and Events Training Package. A wide range of case studies, examples and event profiles from cultural, musical, sporting and corporate events provide students with a full and varied understanding of real-world events